Upaya Pondok Pesantren Dalam Pemberdayaan Santri Melalui Kewirausahaan Di Pondok Pesantren Nurul Hidayah - Abdillah, Syaik; Nulhakim, Lukman (STAI Al Musaddadiyah Garut, 2022)
Nurul Hidayah Islamic Boarding School in Karangtengah Garut is one of the boarding schools based on entrepreneurship. It is not only focused on religious education but also teaches its students entrepreneurship skills. The goal is for students to become self-reliant and skilled individuals after leaving the boarding school. In practice, Nurul Hidayah Islamic Boarding School constantly enhances the abilities of all its students, ensuring they not only understand but also practically apply and master the skills. The issue addressed in this study is the empowerment efforts of entrepreneurial-based students at Nurul Hidayah Islamic Boarding School. The researcher conducted field research to collect data, employing methods such as interviews, observations, and documentation to gather information about entrepreneurial empowerment at Nurul Hidayah Islamic Boarding School. After gathering all the data, the researcher analyzed it using deductive thinking methods. The results of the study show three empowerment efforts undertaken at Nurul Hidayah Islamic Boarding School in Karangtengah Garut. Firstly, by creating an atmosphere conducive to bringing out the talents or potential of the students. Secondly, by strengthening the talents and potential of the students in entrepreneurship. Thirdly, by increasing the participation interest of the students through the implementation of various regulations that require students to participate in entrepreneurial activities at the boarding school. Keywords: Empowerment, Entrepreneurship, Islamic Boarding School